2017
DOI: 10.1186/s41077-017-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of active (hot-seat) versus observer roles during simulation-based training on stress levels and non-technical performance: a randomized trial

Abstract: BackgroundActive ‘hands-on’ participation in the ‘hot-seat’ during immersive simulation-based training (SBT) induces stress for participants, which is believed to be necessary to improve performance. We hypothesized that observers of SBT can subsequently achieve an equivalent level of non-technical performance as ‘hot-seat’ participants despite experiencing lower stress.MethodsWe randomized 37 anaesthesia trainees into two groups to undergo three consecutive SBT scenarios. Eighteen ‘hot-seat’ trainees actively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Limited studies have demonstrated the benefit of simulation observation; however, factors that affect observational learning have yet to be defined. To date, most simulation studies have had observers use structured observation tools, such as CA checklists, to activate them during the experience .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Limited studies have demonstrated the benefit of simulation observation; however, factors that affect observational learning have yet to be defined. To date, most simulation studies have had observers use structured observation tools, such as CA checklists, to activate them during the experience .…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan et al., for example, demonstrated no learning differences between participants and observers; however, observer activation was augmented by the use of CA checklists to critique participant performance while watching the scenario unfold. Bong et al . promoted observer activation by having the observer believe that he or she might be called upon to assist within the scenario while observing directly in the patient encounter room.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations